Compartmented neuronal cultures reveal two distinct mechanisms for alpha herpesvirus escape from genome silencing. - Orkide O Koyuncu; Margaret A MacGibeny; Ian B Hogue; Lynn W Enquist (PLoS Pathogens, 2017)
Alpha herpesvirus genomes encode the capacity to establish quiescent infections (i.e. latency) in the peripheral nervous system for the life of their hosts. Multiple times during latency, viral genomes can reactivate to start a productive infection, enabling spread of progeny virions to other hosts. Replication of alpha herpesviruses is well studied in cultured cells and many aspects of productive replication have been identified. However, many questions remain concerning how a productive or a quiescent infection is established. While infections in vivo often result in latency, infections of dissociated neuronal cultures in vitro result in a productive infection unless lytic viral replication is suppressed by DNA polymerase inhibitors or interferon. Using primary peripheral nervous system neurons cultured in modified Campenot tri-chambers, we previously reported that reactivateable, quiescent infections by pseudorabies virus (PRV) can be established in the absence of any inhibitor. Such infections were established in cell bodies only when physically isolated axons were infected at a very low multiplicity of infection (MOI). In this report, we developed a complementation assay in compartmented neuronal cultures to investigate host and viral factors in cell bodies that prevent establishment of quiescent infection and promote productive replication of axonally delivered genomes (i.e. escape from silencing). Stimulating protein kinase A (PKA) signaling pathways in isolated cell bodies, or superinfecting cell bodies with either UV-inactivated PRV or viral light particles (LP) promoted escape from genome silencing and prevented establishment of quiescent infection but with different molecular mechanisms. Activation of PKA in cell bodies triggers a slow escape from silencing in a cJun N-terminal kinase (JNK) dependent manner. However, escape from silencing is induced rapidly by infection with UVPRV or LP in a PKA- and JNK-independent manner. We suggest that viral tegument proteins delivered to cell bodies engage multiple signaling pathways that block silencing of viral genomes delivered by low MOI axonal infection.